Top management team networking as an imperative predictor of the firm performance: A case of permodalan nasional berhad invested companies - M. Salleh, Sri S. M.; Fareed, Muhammad; Yusoff, Rushami Zien; Saad, Rohaizah (International Economic Society, 2016)
Networking is an important medium in reaching different resources and facilitating the information exchange.Therefore, the integration of various resources within Top Management Team (TMT) through networking is an essential aspect to boost the firm performance. While earlier literature has emphasised the empirical concerns on the influence of networking on firm performance, some have also upstretched concern relating to the impact of TMT towards the firm outcome. Despite its apparent importance, relatively little research has addressed networking as a critical factor for firm performance.Therefore, this study intended to fill this gap by studying the effect of TMT networking on firm performance of Permodalan Nasional Berhad (PNB) invested companies in Malaysia. Data was collected through survey questionnaire from 45 TMT leaders of 45 PNB invested companies and it was analysed using SmartPLS3 through the assessment of measurement model for testing the reliability and validities of the measurement and the assessment of structural model for hypothesis testing. Results indicated that TMT networking, measured as the knowledge embedded within the TMT, within and across the organization, as well as with individuals and organizations outside the firm, has a strong positive effect on firm performance. The results therefore emphasized the importance of TMT backgrounds specifically networking as an essential factor for firm performance. Findings of the study has added into the Upper Echelon Theory. The study is important for practitioners, PNB invested companies and also for PNB since it offers further suggestions and guidelines for the importance of TMT networking for improving the firm performance.